Moderasi Beragama sebagai Ladang Misi Gereja di Era Pluralistik - Dimetria Runtuwene (PT. Giat Konseling Nusantara, 2026)
In the context of an increasingly pluralistic society, the church's mission is required to move from an exclusive approach to a dialogical, contextual, and loving testimony. Religious moderation, with values such as tolerance, anti-violence, openness to local culture, and national commitment, provides a safe and productive space for the church to present the Gospel without triggering identity conflicts. Through this approach, the church can carry out its mission not only through verbal proclamation, but also through real actions that fight for justice, peace, and common welfare. Thus, religious moderation is not an obstacle, but rather a strategic opportunity for the church to remain relevant and transformative in a pluralistic society. In this study, the researcher used qualitative research with a literature study method and the scientific sources used were relevant to the discussion of this article.